Cementless versus Cemented Fixation in Total Knee Arthroplasty: Usage, Costs, and Complications during the Inpatient Period - Gwam, Chukwuweike U.; George, Nicole E.; Etcheson, Jennifer I.; Rosas, Samuel; Plate, Johannes F.; Delanois, Ronald E. (The Journal of Knee Surgery, 2019)
Cemented fixation has been the gold standard in total knee arthroplasty (TKA). However, with younger and more active patients requiring TKA, cementless (press-fit) fixation has sparked renewed interest. Therefore, we investigated differences in (1) patient demographics, (2) inpatient costs, (3) short-term complications, and (4) discharge disposition between patients who underwent TKA with cemented and cementless fixation. The National Inpatient Sample database was queried for TKA patients with cement or cementless fixation between October 1 and December 31, 2015. Primary outcomes of interest included complications, length of stay (LOS), discharge disposition, and inpatient costs. Student's t-test and chi-square analysis were used to assess continuous and categorical data, respectively. Multivariable analysis evaluated the effects of fixation type on the continuous and categorical dependent variables. Patients who received cementless fixation were more often younger (63.5 vs. 65.9 years), male (47.4 vs. 40.3%), Black (10.7 vs. 7.7%), from the Northeast census region (29.1 vs. 17.1%), and under private insurance (49.2 vs. 40.3%; p < 0.001 for all). Cementless fixation involved higher inpatient hospital costs (US$17,357 vs. US$16,888) and charges (US$67,366 vs. US$64,190; p < 0.001 for both), lower mean LOS (2.63 vs. 2.71 days; p < 0.001), and higher odds of being discharged to home (odds ratio = 1.99; p = 0.002). This study revisited the outcomes of TKA with cementless fixation and demonstrated higher inpatient charges and costs, shorter mean LOS, and higher odds of being discharged home. Future studies should investigate patient outcomes and complications past the inpatient period, evaluate long-term survivorship and failure rates, and implement a prospective study design.
Keywords: cementless fixation; cementless total knee arthroplasty; total knee arthroplasty; cost